TRACKING FUTURE TRENDS OF HIV PREVALENCE AMONG INDIVIDUALS AGED 15-49 YEARS IN GUINEA BISSAU USING HOLT’S LINEAR METHOD - Dr. Smartson. P. NYONI; Thabani NYONI (Web of Journals Publishing, 2024)
This study uses annual time series data of HIV prevalence among individuals aged 15-49 years for Guinea Bissau from 1990 to 2020 to predict future trends of HIV prevalence over the period 2021 to 2030. The study utilizes Holt’s linear exponential smoothing model. The optimal values of smoothing constants α and β are 0.9 and 0.5 respectively based on minimum MSE. The results of the study indicate that annual HIV prevalence among individuals aged 15-49 years will continue to decline over the out of sample period. Therefore, it is critical to direct more effort on improving ART retention and adherence especially among adolescents to minimize treatment failure.
Keywords: Exponential smoothing, Forecasting, HIV prevalence.